Synergistic and Additive Effect of Oregano Essential Oil and Biological Silver Nanoparticles against Multidrug-Resistant Bacterial Strains - Scandorieiro, Sara; de Camargo, Larissa C.; Lancheros, Cesar A. C.; Yamada-Ogatta, Sueli F.; Nakamura, Celso V.; de Oliveira, Admilton G.; Andrade, Célia G. T. J.; Duran, Nelson; Nakazato, Gerson; Kobayashi, Renata K. T. (Frontiers in Microbiology, 2016)
Bacterial resistance to conventional antibiotics has become a clinical and public health problem, making therapeutic decisions more challenging. Plant compounds and nanodrugs have been proposed as potential antimicrobial alternatives. Studies have shown that oregano (Origanum vulgare) essential oil (OEO) and silver nanoparticles have potent antibacterial activity, also against multidrug-resistant strains; however, the strong organoleptic characteristics of OEO and the development of resistance to these metal nanoparticles can limit their use. This study evaluated the antibacterial effect of a two-drug combination of biologically synthesized silver nanoparticles (bio-AgNP), produced by Fusarium oxysporum, and OEO against Gram-positive and Gram-negative bacteria, including multidrug-resistant strains. OEO and bio-AgNP showed bactericidal effects against all seventeen strains tested, with minimal inhibitory concentrations (MIC) ranging from 0.298 to 1.193 mg/mL and 62.5 to 250 µM, respectively. Time-kill curves indicated that OEO acted rapidly (within 10 min), while the metallic nanoparticles took 4 h to kill Gram-negative bacteria and 24 h to kill Gram-positive bacteria. The combination of the two compounds resulted in a synergistic or additive effect, reducing their MIC values and reducing the time of action compared to bio-AgNP used alone, i.e., 20 min for Gram-negative bacteria and 7 h for Gram-positive bacteria. Scanning electron microscopy (SEM) revealed similar morphological alterations in Staphylococcus aureus (non-methicillin-resistant S. aureus, non-MRSA) cells exposed to three different treatments (OEO, bio-AgNP and combination of the two), which appeared cell surface blebbing. Individual and combined treatments showed reduction in cell density and decrease in exopolysaccharide matrix compared to untreated bacterial cells. It indicated that this composition have an antimicrobial activity against S. aureus by disrupting cells. Both compounds showed very low hemolytic activity, especially at MIC levels. This study describes for the first time the synergistic and additive interaction between OEO and bio-AgNP produced by F. oxysporum against multidrug-resistant bacteria, such as MRSA, and β-lactamase- and carbapenemase-producing Escherichia coli and Acinetobacter baumannii strains. These results indicated that this combination can be an alternative in the control of infections with few or no treatment options.